Menelusuri Keberhasilan Implementasi Kebijakan QRIS dalam Sistem Retribusi Parkir Kota Surabaya - Rachmawati Novaria (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2024)
This research explores the effectiveness of the Surabaya City Government’s policy on parking levy payments via the Quick Response Code Indonesian Standard (QRIS). The study aims to analyze the policy’s success in increasing Regional Original Income (Pendapatan Asli Daerah or PAD) and enhancing community welfare by improving the payment experience for parking users and supporting efficient management by parking attendants. Using Van Meter and Van Horn’s policy implementation framework, which includes six critical factors—policy standards and objectives, resource allocation, characteristics of implementing organizations, inter-organizational communication, implementer disposition, and socio-political and economic environment—the study evaluates both the facilitating and hindering elements of the policy. A qualitative descriptive methodology was employed, with data gathered through literature reviews, field observations, and structured interviews with key stakeholders, including government officials, parking service providers, and users. Analysis revealed that QRIS implementation has been beneficial in promoting transparency and efficiency in revenue collection, supporting PAD growth. However, challenges such as varying levels of digital literacy among users, limited internet access in certain areas, and reluctance among some parking attendants to adopt digital systems were identified as barriers to optimal implementation. Key findings suggest that the policy’s long-term success hinges on consistent inter-agency coordination, community engagement initiatives to raise digital payment awareness, and ongoing training for parking attendants to improve digital proficiency. The study concludes that achieving sustainable success in implementing non-cash transactions for parking levies requires a holistic approach, integrating community awareness, inter-organizational support, and policy adaptability. This research offers valuable insights for policymakers seeking to improve public service delivery through digital transactions. It highlights the importance of adaptive management in fostering community welfare alongside regional revenue growth.